You will know them by their movement: evaluating pain and mobility behavior in preclinical models of post-traumatic and infection-associated osteoarthritis - Kloser, Heidi, author; Santangelo, Kelly, advisor; Henao-Tamayo, Marcela, advisor; Dobos, Karen, committee member; Goodrich, Laurie, committee member (Colorado State University. Libraries, 2025)
Osteoarthritis (OA) is a progressive, multifactorial joint disease affecting an estimated 595 million people globally and is the leading cause of disability in the United States. Characterized by cartilage degradation, subchondral bone remodeling, and synovial inflammation, OA leads to pain, stiffness, and loss of mobility. These factors further contribute to comorbidities such as cardiovascular disease, metabolic dysfunction, and early mortality. While aging and female sex are primary risk factors, OA can also be triggered or exacerbated by joint trauma, repetitive stress, obesity, and systemic inflammation. Despite current therapies, an estimated 20-50% of joint injuries will typically progress to clinical post-traumatic osteoarthritis (PTOA) within 10-20 years, underscoring the urgent need for more effective therapies. Emerging evidence also implicates infectious diseases, including tuberculosis (TB), as potential facilitators of joint degeneration. To better understand these complex interactions, this work employed longitudinal assessments of pain and mobility behaviors to evaluate disease onset and progression across preclinical OA models. This dissertation aims to enhance the translational utility of rodent post-traumatic and infection-associated OA models by refining behavioral and mobility assessments, testing protocols, evaluating the therapeutic efficacy of stromal cell therapy and PTOA, and investigating the potential for infectious diseases to exacerbate joint degeneration. Chapter 1 presents a comprehensive review of rodent mobility and pain-related behaviors following destabilization of the medial meniscus (DMM) injury. This chapter highlights significant behavioral differences between injured and control animals in these PTOA models, identifies timelines for when changes are expected to occur, and provides a comprehensive summary of current efforts to understand behavioral and pain responses post-injury. Additionally, this review emphasizes the importance of standardizing and improving communication within the field to enhance reproducibility and translational relevance. Chapter 2 builds upon the behavioral insights presented in Chapter 1 by providing an in-depth analysis of short-term open-field testing in mice. This work establishes foundational behavioral profiles for naïve juvenile and adult male and female mice, offering evidence-based recommendations for optimal test durations and parameter selection. These findings support the refinement of behavioral assessments in preclinical research. Chapters 3 and 4 apply behavioral and pathological outcome measures to evaluate the effects of therapeutic and comorbid modifiers of OA. Chapter 3 investigates the potential of stromal cell therapies to modulate inflammation and improve clinical indicators of PTOA. Chapter 4 examines how chronic pulmonary TB infection affects joint degeneration and mobility-related behaviors in animal models, providing new insights into the pathogenesis of infection-associated OA. Chapter 5 concludes the dissertation by integrating the findings across studies, underscoring how behavioral outcomes are interconnected across different models and interventions. This work discusses the broader implications for the field and proposes future directions, including the development of composite behavioral scoring systems to enhance consistency and interpretability in OA research.
Keywords: infectious disease; osteoarthritis; stromal cell therapies; mobility; behavior; pain